Electronic excitation induced hydrogen-bond adjustment and lattice control in organic–inorganic hybrid cubic perovskites: a fixed occupation molecular dynamics study. Issue 38 (20th September 2017) - Wang, Mo-Ran; Ren, Xiang-Yang; Li, Xian-Bin; Chen, Nian-Ke; Sun, Hong-Bo
Abstract : Fixed occupation first-principles study reveals the effect of electronic excitation on lattice of cubic perovskite MAPbI3 . With excitations, the hydrogen bonding between MA molecules and inorganic lattice is weakened and the cubic symmetry is recovered. Abstract : The organic–inorganic hybrid perovskite has become a new type of semiconductor for low cost and highly efficient solar cells. However, the mechanism of interactions between the organic cation and the inorganic framework is still not completely clear under optical electronic excitation. In this work, we employ first-principles molecular dynamics with electronic excitation effects to prove that the hydrogen-bond interaction between the molecular cation and the inorganic lattice can be readily adjusted by several-percentage-valence-electron excitations in cubic CH3 NH3 PbI3 . While the hydrogen-bond interaction causes serious lattice distortions, the electronic excitation can recover the lattice symmetry largely by weakening hydrogen bonding. The study offers atomic dynamics to understand the excitation process in the organic–inorganic hybrid perovskite semiconductor.